(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
This article discusses ideas and reflections on the formation of students’ creative competence based on STEAM education. In today’s rapidly evolving world, creative competence has become an essential skill for students. Not only does it enhance their ability to think innovatively, but it also prepares them for a workforce that increasingly values problem-solving, adaptability, and interdisciplinary thinking. One effective approach to nurturing creative competence is through STEAM education, which integrates Science, Technology, Engineering, Arts, and Mathematics into a cohesive learning framework.